PHYSIOLOGICAL FUNCTIONAL STATES OF MITOCHONDRIA IN THE THERMODYNAMIC AND ELECTROCHEMICAL CYCLE - S. N. Alekseenko; A. S. Tatevosyan; A. V. Bunyakin; V. G. Zolotukhina; R. G. Kazarov (Кубанский научный медицинский вестник, 2018)
Aim. This study was performed to identify the possible physiological and pathogenetic processes taking place in the mitochondrial matrix which create the conditions for lithogenesis of insoluble calcium phosphate salts (calcium carbonate...). Whereas, they can later be deposited in various tissues, taking into account the fact that the formation of calcium phosphate (calcium carbonate ...) in the human body occurs under normal physiological conditions (bone tissue, otolith...). It raises the urgency of the question of understanding the physiological and pathogenetic mechanisms of lithogenesis.Materials and methods. There was carried out a meta-analysis of the functional states of mitochondria, to which we 125 Kubanskij nauchnyj medicinskij vestnik 2018; 25 (5) applied a mathematical model based on the changing direction and velocity of the conjugated thermodynamic and electrochemical parameters (pressure, volume, temperature, Gibbs potential, exergy…). Considering the schemes of the oxidative phosphorylation proposed by R.Mitchell and R.Williams, we created a model of the thermodynamic and electrochemical cycle of mitochondria which gives a deeper understanding of the principles of the mechanisms of the ongoing processes in the system mitochondrial matrix-internal membrane-intermembrane space.Results. Based on the fundamental principle of functional interaction, there were proposed four functional states of mitochondria (M) in thermodynamic and electrochemical (TD-EC) cycle, to which was created a mathematical model that allows to systematize the processes accompanied by the accumulation of the electrochemical potential, in other words, the charge separation (ionization) in the paramembrane space. At the same time, on the one side of the inner membrane (mitochondrial intermembrane space) the positive charge predominates, and on the other side (the mitochondrial matrix) – the negative. These processes, in view of the repulsion of like charges, lead to the increase in pressure both in the mitochondrial matrix and in the intermembrane space. In this sense, the direction of the electrochemical processes, taking place in the intramembrane and intermembrane environment from the position of physical thermodynamics, is similar to the direction of the processes occurring in the compressible ionized gas (plasma).The states of mitochondria are considered when the velocity of electrons along the respiratory chain, which is associated with a change in the thermal potential, changes in the thickness of its internal membrane. For the medium inside the matrix, which is an ultra-microheterogeneous dispersive mass, and also using the thermodynamic analogy with the ionized gas, by the thermal potential (Ǫ) we mean the product of pressure (P) per volume (V): Ǫ= PV. Based on the mathematical model of the thermodynamic behavior of the mitochondria and on the limitations imposed by the laws of physical and chemical thermodynamics, it is established that the greatest degree of thermodynamic perfection in the process of mitochondrial respiration corresponds to the state of "respiratory control" which, among the set of Functional States, is acceptable to consider the fundamental (basic, the first), in other words, F-I.The hierarchy of the homeostatic system of mitochondria is built according to the degree and speed of energy consumption which constantly switches (fluctuates ...) because life is the consequence of a stable nonequilibrium state of the special molecules, since living systems are never in equilibrium and, due to their free Gibbs energy (G), perform a constant work against the equilibrium.There is a physiological "balance" between the various functional states competing for the mitochondrial energy resources: 1) involuntary (Gibbs potential G>0) endergonic phosphorylation process which triggers ATP synthase and is accompanied by the cooling; and 2) spontaneous (Gibbs potential G<0) exergonic process that increases the temperature of the external medium. The pathophysiological "unbalance" of these mechanisms, in which the conditions for the formation of the watersoluble salt of calcium phosphate dihydrate-Ca (H2 PO4 )2 interchange with the poorly soluble calcium hydrogenphosphateСаHPO4 , can be a pathogenetic cause of the occurrence of common diseases (nephrolithiasis, osteochondrosis, atherosclerosis ...).Conclusion. In the thermodynamic and electrochemical cycle of the mitochondrial system matrix-internal membraneintermembrane space, the direction and speed of physiological functional variables, which determine the presence and magnitude of the primary physiological needs, are important. In the multidimensional space of the physiological functional variables there is a gap of functionality. This is the range of parameters variations, the limits of which are distributed according to Gauss and are optimal for the habitat mode in the external environment, which is the cytoplasm in regards to the mitochondria. Going beyond the limits of the gap of functionality promotes the thermodynamic and electrochemical adaptation changes in the mitochondrial system itself which tends to return to the state of the thermodynamic "rest", while the mitochondria performs a cyclic process.Relying on the fact that the fundamental principle of the functional expediency establishes the primacy of the maximum residence time of any living system in the defined ("normative", "permissible" ...) limits of the functionality gap, the fluctuations of which are conditioned by the changing external conditions and internal needs, we express confidence that, taking into account the limitations imposed by the laws of physical and chemical thermodynamics, the greatest degree of thermodynamic perfection of the mitochondrial breathing process in the dynamical electrochemical cycle is performed in the state of the respiratory control (F-I), which corresponds to the maximum entropy (S) and the minimum Gibbs energy (G). In the thermodynamic and electrochemical cycle may arise the conditions that include the adaptive biochemical changes that favor the accumulation of Ca2+ in the mitochondrial matrix, and thereby confirm the direct dependence of the calcium retention capacity on the speed of the respiration of mitochondria. At the same time, a significant amount of Ca2+ accumulates in the mitochondrial matrix, which, combined with the hydrophosphate, is transformed into the calcium diphosphate − Ca3 (PO4 )2 , which has an extremely low solubility in water. This may be a primordial mechanism of lithogenesis with the subsequent deposition of calcium phosphate salts in various tissues, causing the diseases at the organ level, in the pathogenesis of which the violation of energy metabolism is common!